Immunoproteasome Function in Normal and Malignant Hematopoiesis - Nuria Tubío-Santamaría (Cells, 2021)
The ubiquitin–proteasome system (UPS) is a central part of protein homeostasis, degrading not only misfolded or oxidized proteins but also proteins with essential functions. The fact that a healthy hematopoietic system relies on the regulation of protein homeostasis and that alterations in the UPS can lead to malignant transformation makes the UPS an attractive therapeutic target for the treatment of hematologic malignancies. Herein, inhibitors of the proteasome, the last and most important component of the UPS enzymatic cascade, have been approved for the treatment of these malignancies. However, their use has been associated with side effects, drug resistance, and relapse. Inhibitors of the immunoproteasome, a proteasomal variant constitutively expressed in the cells of hematopoietic origin, could potentially overcome the encountered problems of non-selective proteasome inhibition. Immunoproteasome inhibitors have demonstrated their efficacy and safety against inflammatory and autoimmune diseases, even though their development for the treatment of hematologic malignancies is still in the early phases. Various immunoproteasome inhibitors have shown promising preliminary results in pre-clinical studies, and one inhibitor is currently being investigated in clinical trials for the treatment of multiple myeloma. Here, we will review data on immunoproteasome function and inhibition in hematopoietic cells and hematologic cancers.